Epidendra Nova Talamancana - Díaz-Morales, Melissa; Karremans, Adam P. (Phytotaxa, 2016)
Two new species of Epidendrum from the Costa Rican montane rainforest, E. hartmanniorum and E. vallis-silentii, are described, illustrated and compared with similar species. Epidendrum stolidium and E. unicallosum are reported as new records of this genus for the country.